Superconductivity in Weyl semimetals with time reversal symmetry - Xuesong Bai; W LiMing; Tao Zhou (New Journal of Physics)
This theoretical study delves into the superconducting traits of Weyl semimetals that possess time reversal symmetry, utilizing the Bogoliubov–de Gennes equations. Our meticulous self-consistent calculations have unveiled a dual superconducting gap at the surface. We have also contrasted these findings with the superconducting characteristics of models that exhibit broken time-reversal symmetry. Our analysis indicates that Weyl semimetals with unimpaired time-reversal symmetry not only sustain a complete energy gap but also display modified Fermi arc surface states, which are notably distinct from those in models with compromised time-reversal symmetry. This work bridges the gap between theoretical expectations and experimental observations, advancing our understanding of the superconducting properties of Weyl semimetals.